CIMPACT‐NOW: a practical summary of diagnostic points from Round 1 updates. (22nd May 2019) - Louis, David N.; Ellison, David W.; Brat, Daniel J.; Aldape, Kenneth; Capper, David; Hawkins, Cynthia; Paulus, Werner; Perry, Arie; Reifenberger, Guido; Figarella‐Branger, Dominique; von Deimling, Andreas; Wesseling, Pieter
Abstract: cIMPACT‐NOW (the Consortium to Inform Molecular and Practical Approaches to CNS Tumor Taxonomy) was established to provide a forum to evaluate and recommend proposed changes to future CNS tumor classifications. From 2016 to 2019 (Round 1), cIMPACT published four updates. Update 1 clarified the use of the term NOS (Not Otherwise Specified) and proposed use of the additional term NEC (Not Elsewhere Classified). Update 2 issued clarifications regarding two diagnoses: Diffuse Midline Glioma, H3 K27M‐mutant and Diffuse Astrocytoma/Anaplastic Astrocytoma, IDH‐mutant . Update 3 proposed molecular criteria that could be used in the setting of an IDH‐wildtype diffuse or anaplastic astrocytic glioma without histological features of glioblastoma to infer that the tumor would behave similarly to a grade IV glioblastoma. Update 4 suggested that, in children and young adults, subtypes of IDH‐wildtype/H3‐wildtype diffuse gliomas may have distinct clinical features in the setting of a BRAF V600E mutation, FGFR1 alteration, other MAPK pathway alteration, or a MYB or MYBL1 rearrangement. The practical diagnostic relevance of these cIMPACT proposals is highlighted in this summary.